Maternal Age and Parity As Risk Factors Affecting The Incidence of Iron Deficiency Anemia in Pregnant Women in The Working Area of The Bungus Health Center, Padang City - Sri Astuti Siregar; Febby Oktariani; Asparian Asparian; Usi Lanita; La Ode Reskiaddin (The International Science of Health Journal, 2023)
Anemia is a serious health problem in pregnant women because red blood cells play an important role in distributing supplements and oxygen for fetal development. Based on WHO data (2019), the number of people in the world who suffer from anemia is more than 2 billion people or 30% of the total population. Pregnant women who experience anemia worldwide reach 41.8%. The prevalence of anemia in pregnant women at the Bungus Community Health Center in 2021 is 36% and is the highest incidence of anemia among all community health centers in Padang City. Among the risk factors that cause iron deficiency anemia in pregnant women are age and parity. This research uses quantitative methods through a cross sectional approach with a sample of 67 pregnant women in the Bungus Community Health Center working area. Random sampling technique proportional simple random sampling and data analysis using tests Chi-Square. The results of the study showed that there was a relationship between maternal age (p=0,046) with the incidence of anemia, while parity showed no significant relationship (p=0,119). It is hoped that Bungus Community Health Center officers can increase intensive outreach strategies so that the incidence of anemia in pregnant women can be prevented from an early age.